Right Atrial Mechanics in Children with Pulmonary Arterial Hypertension Associated with Congenital Heart Disease - Gamze Vuran; Timur Meşe; Murat Muhtar Yılmazer; Engin Gerçeker; Cüneyt Zihni (Galenos Publishing House, 2024)
Objective: This study aims to evaluate right atrial functions in children with pulmonary arterial hypertension (PAH) associated with congenital heart disease (CHD) by deformation indices assessed by two dimensional-speckle tracking echocardiography. Method: A total of 40 patients, including 15 patients with World Health Organization Functional class II-III CHD-PAH and 25 age-matched healthy controls were enrolled in the study. Deformation indices were measured by electrocardiogram-gated right atrial longitudinal strain recordings. Results: Peak atrial strain/reservoir phase (24.19±15.81 vs. 40.62±12.35%,) (p=0.01), conduit phase (15±00.13.6% vs. 26.4±10.7%) (p=0.006) and pump phase (10.06±9.07% vs. 14.21± 5.05%) (p=0.07) were comparatively evaluated in the patient and control groups, respectively Regional peak atrial strain measurements performed for basal anterolateral (p=0.06), mid anterolateral (p=0.12), apical anterolateral (p=0.61), apical inferoseptal (p=0.28) and mid inferoseptal (p=0.001), basal inferoseptal (p=0.02) segments were also compared between the patient and control groups. Conclusion: Right atrial deformation indices were significantly impaired in patients with CHD-PAH. Deterioration in the right atrial reservoir and conduit functions are associated with right ventricular diastolic dysfunction. Both global and regional changes can be observed in the measurement of right atrial strain secondary to the existing heart defects and operative conditions of the patients.